2022
DOI: 10.1007/s10967-022-08420-z
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of ruthenium in nitric media (HLLW) in reprocessing plants: a review and some perspectives

Abstract: The reprocessing of spent nuclear fuel produces high level liquid waste (HLLW). Due to the decay heat, the concentrated nitric solutions containing fission products (FP) are stored in cooled tanks. Actually, the loss-of-cooling accident on these HLLW storage tanks could lead to releases of radioactive materials to the environment, especially ruthenium volatile species.After a general presentation on the physico-chemical behaviour of ruthenium in concentrated nitric acid, this paper successively details the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…So, this work highlights same tendencies observed before by Ishio et al [14]. For more complete information, a recent literature review is available [6].…”
Section: Literature Reviewsupporting
confidence: 88%
See 2 more Smart Citations
“…So, this work highlights same tendencies observed before by Ishio et al [14]. For more complete information, a recent literature review is available [6].…”
Section: Literature Reviewsupporting
confidence: 88%
“…Even if the probability of occurrence of such an accident remains low, several mitigation systems have already been developed since the design of the process and can still be improved. A review of the studies carried out on this accident scenario in the design stage confirmed the lack of reliable data on the behaviour of ruthenium [6]. It also highlighted the limits of the models used at the time to evaluate the source term.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Other experiments realized on the same experimental setup and under the same conditions with sand, silver-doped zeolites, and activated charcoal showed a very low decontamination below 4. 7,41 So, UiO-66-NH 2 is a much more promising material for the filtration of RuO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Second, nitrogen oxides are of special interest regarding ruthenium chemistry. RuO4 is known for its ability to form different nitroso and nitrosyl compounds after reacting with nitric acid, NO2 or NO gases [5][6][7]. RuO4 can also be trapped into the water phase after reacting with NO2 or NO gases [8].…”
Section: Introductionmentioning
confidence: 99%